Pengembangan LKPD Berbasis Project Based Learning (PjBL) Berbantuan Kit Robot Maze Solver (Labirin) pada Materi Mikrokontoler Arduino - Rona Pinta Uli Debata Raja; Nehru; Jules Nurhatmi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Arduino microcontroller learning requires not only conceptual understanding but also practical skills in designing, assembling, programming, and testing hardware-based systems. However, students often experience difficulties in understanding Arduino programming concepts when learning is not supported by project-based activities and appropriate practical learning media. This study aimed to develop a Project Based Learning (PjBL)-based Student Worksheet (LKPD) assisted by a maze solver robot kit on Arduino microcontroller material. This study employed the Research and Development (R&D) method using the Four-D (4D) development model consisting of the Define, Design, Develop, and Disseminate stages. The subjects were 12 students of the Physics Education Study Program, Faculty of Teacher Training and Education, Universitas Jambi, who had taken the Advanced Electronics course. Data were collected through media expert validation questionnaires, material expert validation questionnaires, robot kit expert validation questionnaires, and student perception questionnaires. Quantitative data were analyzed using percentage techniques, while qualitative data in the form of suggestions and feedback from validators were used as the basis for product revision. The results showed that the developed LKPD obtained a feasibility percentage of 80.77% from media experts, 100% from material experts, and 91.07% from robot kit experts, all categorized as highly feasible. Student perceptions yielded an average percentage of 89%, categorized as very good. The developed LKPD is expected to serve as an innovative teaching material that supports project-based learning and enhances student engagement in learning Arduino microcontrollers.